Efektivitas Penerapan Diet DASH Pada Penderita Hipertensi: Literature Review - Kolinug, Christina Millenia; Kundre, Rina Margaretha; Larira, Dina Mariana (Mapalus Nursing Science Journal, 2024)
Background. In prevention and treatment efforts that need to be carried out in hypertension sufferers are lifestyle modifications. By improving your diet by reducing consumption of foods that are high in sodium and fatty foods. So it is recommended regarding diet, namely setting a daily Dietary Approach to Stop Hypertension (DASH) diet. Objective. To determine the effectiveness of implementing the DASH diet in hypertension sufferers. Method: This type of research is a Literature Review study using 2 e-resource databases, namely Google Scholar and Pubmed. Results. 4 journals/articles were obtained that met the criteria. Where the application of the DASH diet to hypertension sufferers has an effect on reducing blood pressure. Conclusion. In this research, the DASH diet can be an option for lowering blood pressure in hypertension suffers. Where the DASH diet is recommended to reduce consumption of salt and is recommended to consume vegetables, fruit, low-fat dairy products, seeds, nuts, and lean meat, poultry and fish, in regulated portions.    Keywords: DASH Diet, Hypertension,Lifestyle